Montagens e desmontagens: vergonha, estigma e desejo na construção das travestilidades na adolescência - Duque, Tiago (2009)
This research analyses some teenager travestilities in a social net in the city of Campinas, State of São Paulo, Brazil. The thesis follows a Queer theoretical approach with an ethnographic field that united observation, face to face interviews and also via Messenger and Orkut (an online social site). It focus on new travestilities identity processes that have been built with different references in comparison to older generations of Brazilian travesties: especially less interest in following the motto of being dressed like a woman 24 hours and a restriction in the use of liquid silicon. These teenagers have tried to manipulate their social identities in a tatic and sometimes strategic way - through a process of building the feminine with the use of clothes, wigs and other accessories (montage) and taking them off to present themselves in a masculine performance (desmontagem). We adopt a historical and contextual perspective to understand how these teenager experiences marked by stigma and shame expresses ways of dealing with the closet apparatus. This perspective also emphasizes a sociological comprehension of their subjectivities. The thesis shows a preliminary analysis of how these new body and subjective experiences constitute a mix of resistance and insertion in hegemonic codes of sexuality and gender.